Correction: The effect of isohydric hemodialysis on the binding and removal of uremic retention solutes. - Aleksey Etinger; Sumit R Kumar; William Ackley; Leland Soiefer; Jonathan Chun; Prabjhot Singh; Eric Grossman; Albert Matalon; Robert S Holzman; Bjorn Meijers; Jerome Lowenstein (PLoS ONE, 2018)
[This corrects the article DOI: 10.1371/journal.pone.0192770.].